Parenthood and Trajectories of Change in Body Weight Over the Life Course - Umberson, Debra (2011)
Scholars call for greater attention to social contexts that promote and deter risk factors for health. Parenthood transforms social contexts in a myriad of ways that may influence long-term patterns of weight gain. Life course features of parenthood such as age at first birth, parity, and living with a minor child may further influence weight gain. Moreover, the social and biological features of parenthood vary in systematic ways for women and men, raising questions about how social contexts might differentially affect weight patterns by gender. We consider how parenthood influences trajectories of change in body weight over a fifteen year period (from 1986 to 2001) with growth curve analysis of data from the Americans' Changing Lives Survey, conducted with adults aged 24 and older in the contiguous United States (N=3,617). Findings suggest that parents gain weight more rapidly than the childless throughout the study period and that this weight gain occurs for both men and women. Men and women who have their first child earlier or later than about age 27 have accelerated weight gain, living with a minor child is associated with heavier weight for men than women, and parity is associated with greater weight gain for women than men. We conclude that parenthood contributes to a long term, cumulative process of weight gain for American women and men but life course factors that accelerate this process may differ by gender.